Investigation on tension–tension fatigue performances and reliability fatigue life of T700/MTM46 composite laminates. (February 2016) - Feng, Yu; Gao, Chao; He, Yuting; An, Tao; Fan, Chaohua; Zhang, Haoyu
Abstract: Tension–tension fatigue performances of T700/MTM46 composite laminates were investigated in this paper and the fatigue limit was determined. Failure modes of the fatigue specimens are mainly characterized by severe delamination throughout the whole gauge length while the static tension specimens exhibit brittle fractures within a small region. The stiffness degradation shows a quasi-linear slow decline during approximately 0–80% fatigue life and has a sharp decline since 80% fatigue life. Damage evolution was studied by fatigue specimens' edge view, which showed the damage in 90° plies initiate firstly and propagate most seriously during fatigue. The distribution of fatigue life was determined. Single side allowance factor was proposed to calculate the reliability fatigue life with both reliability and confidence level. The results show that reliability fatigue life reduces more when the reliability increases than when confidence level does to the same degree. A new fatigue model ( p – γ – S – N curve) was also established to predict the reliability fatigue life.